ANALISA PENINGKATAN MUTU PENDIDIKAN KARAKTER DAN TAHAPAN-TAHAPANNYA PADA SMK BPPI BALEENDAH DI KABUPATEN BANDUNG - Daeng Ramang (Sinau : Jurnal Ilmu Pendidikan dan Humaniora, 2019)
Vocational high school SMK as a provider of labor both in industry and on other business, developments in the world Industries that produce products that hight tech good for the needs of transportation products, consumer products, toys products, food products and other products, the existence of disagreement between industrial dunnia and education world in schools, especially Vocational High School. As for the industrial world expect in the recruitment of new labor ready to use, so the gap is not singkron, between the needs of skilled labor and the availability of less skilled workers resulting from school education as a printer graduate school as a workforce that is ready to use, a opportunities for educational institutions to be greeted positively.